A sprayable composite hydrogel based on active oxygen response and a preparation method and application thereof

CN122973684APending Publication Date: 2026-10-27SOUTHWEST JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610990146.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该敷料须具备优异的生物相容性与可喷雾性,能够根据创面炎症程度动态释放活性成分,以有效杀灭细菌并促进组织修复,克服现有敷料药物释放不可控、生物相容性差等痛点

Benefits of technology

本发明提出一种基于活性氧响应的可喷雾复合水凝胶及其制备方法与应用,通过构建由氧化透明质酸(OHA)与透明质酸-己二酸二酰肼(HA-ADH)形成的第一动态共价交联网络,以及由聚乙烯醇(PVA)与含苯硼酸基团的交联剂TSPBA形成的第二可逆交联网络,并将特定钴金属离子配合物负载于该双网络复合体系中,有效解决了上述背景技术中的问题。在创面局部高浓度活性氧环境下,第二交联网络中的硼酸酯键发生响应性断裂,触发复合水凝胶网络局部解构,实现钴金属离子配合物的按需释放,避免了常规敷料药物的被动渗漏与全身毒副作用,显著提高了药物的生物利用度;同时,该双网络交联结构赋予了水凝胶良好的剪切变稀特性与可喷雾性,使其能够通过喷涂均匀覆盖于复杂、不规则的创面表面,并迅速原位成胶形成物理屏障,弥补了传统水凝胶难以有效贴合慢性创面及烧伤创面的缺陷,为创面修复提供了一种安全、可控、便捷的智能治疗策略。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122973684A_ABST
    Figure CN122973684A_ABST
Patent Text Reader

Abstract

The application discloses a sprayable composite hydrogel based on active oxygen response and a preparation method and application thereof, and belongs to the technical field of biomedical materials and wound repair; the hydrogel is composed of oxidized hyaluronic acid (OHA) and hyaluronic acid-adipic acid dihydrazide (HA-ADH) through a dynamic hydrazine bond, and polyvinyl alcohol (PVA) and TSPBA containing a phenylboronic acid group through a reversible borate ester bond to form a double-network crosslinking structure; wherein the double-network crosslinking structure is loaded with a cobalt metal ion complex generated by the reaction of 4-methylaminothiourea, alpha-ketoglutaric acid and cobalt chloride. The hydrogel has a shear thinning property, can be in-situ gelled by a spraying method and covered on a wound surface. Under a high ROS microenvironment of the wound surface, the borate ester bond is broken responsively to trigger the release of the cobalt ion complex, so that the local controlled release of drugs is realized; the application overcomes the defects that traditional wound dressings are difficult to adapt to microenvironment changes and have low bioavailability, and can effectively promote the healing of chronic wounds and burn wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the interdisciplinary field of biomedical materials technology, specifically relating to a sprayable composite hydrogel based on reactive oxygen species response, its preparation method, and its application. Background Technology

[0002] The difficulty in healing chronic wounds (such as diabetic foot ulcers and deep burns) and infected wounds is a challenging problem in clinical treatment. The root cause lies in the imbalance of the wound microenvironment: on the one hand, local inflammatory responses lead to abnormally high levels of reactive oxygen species (ROS), causing continuous oxidative stress damage, accompanied by a large amount of exudate; on the other hand, abnormal wound pH and the accumulation of metabolic products provide a breeding ground for bacteria, further hindering the regeneration and repair of normal tissues.

[0003] Currently, commonly used wound management methods in clinical practice mainly rely on alginate dressings, conventional hydrogel dressings, or growth factor coatings. However, these traditional wound dressings have relatively limited functions, mostly only providing physical barrier protection or passive drug release. They struggle to intelligently respond to and regulate drug release rates in response to dynamic changes in the wound microenvironment (such as fluctuations in ROS concentration and pH changes). This leads to premature drug leakage at non-target sites, low bioavailability, or irritation and drug resistance due to excessively high local concentrations. Furthermore, the biocompatibility and fit to irregular wounds of the dressings themselves are significantly insufficient, limiting their widespread clinical application.

[0004] Therefore, there is an urgent need to develop a smart hydrogel dressing that can gel in situ, adapt to irregular wound coverage, and is responsive to the wound microenvironment (especially reactive oxygen species). This dressing must possess excellent biocompatibility and atomability, and be able to dynamically release active ingredients according to the degree of wound inflammation to effectively kill bacteria and promote tissue repair, overcoming the pain points of existing dressings such as uncontrollable drug release and poor biocompatibility. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a sprayable composite hydrogel based on reactive oxygen species response, its preparation method and application.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This application provides a sprayable composite hydrogel based on reactive oxygen species response, the hydrogel comprising: The first cross-linked network containing dynamic hydrazide bonds is formed by the condensation reaction of oxidized hyaluronic acid (OHA) and hyaluronic acid-adipic acid dihydrazide (HA-ADH); A second crosslinked network containing borate ester bonds, formed by a reversible reaction between polyvinyl alcohol (PVA) and the crosslinking agent TSPBA containing phenylboronic acid groups; and Cobalt metal ion complex loaded in a composite network composed of the first cross-linking network and the second cross-linking network; In an active oxygen environment, the borate ester bonds in the hydrogel break, triggering the responsive release of the cobalt metal ion complex.

[0007] Furthermore, the coordination precursor in the cobalt metal ion complex is generated by a nucleophilic addition reaction of 4-methylaminothiourea and α-ketoglutaric acid, and the coordination precursor and divalent cobalt ions are coordinated to form the cobalt metal ion complex.

[0008] Furthermore, the first cross-linked network and the second cross-linked network interpenetrate and overlap each other to form a dual-network cross-linked structure with a synergistic enhancement effect.

[0009] Furthermore, the hydrogel exhibits shear-thinning properties, exhibiting a flowable fluid state under shear stress and reverting to a gel state after the shear stress is removed.

[0010] A method for preparing a sprayable composite hydrogel based on reactive oxygen species, as described above, includes the following steps: (1) Oxidized hyaluronic acid (OHA) and hyaluronic acid-adipic acid dihydrazide (HA-ADH) are mixed and reacted in an aqueous medium to form an initial hydrogel network containing dynamic hydrazide bonds; (2) Add polyvinyl alcohol (PVA) and crosslinking agent TSPBA containing phenylboronic acid groups to the system obtained in step (1), mix and react to form a composite crosslinking network containing reversible borate ester bonds; (3) Introduce the cobalt metal ion complex into the composite system obtained in step (2) and disperse it evenly in the system. Let it stand to form a gel to obtain the composite hydrogel.

[0011] Furthermore, the reactions in steps (1) and (2) are carried out under aqueous conditions and at temperatures ranging from room temperature to 37°C.

[0012] Furthermore, the preparation process of the cobalt metal ion complex includes: dissolving 4-methylaminothiourea and α-ketoglutaric acid in organic solvents respectively to carry out substitution reactions to obtain ligand solutions; mixing the ligand solutions with cobalt metal salt solutions, adjusting the pH to alkaline conditions to carry out coordination reactions, and separating and purifying the mixture after the reaction to obtain the cobalt metal ion complex.

[0013] Application of hydrogels in the preparation of medical dressings for wound repair.

[0014] Furthermore, in step (2), the mixing system is formed by mixing a first mixing precursor and a second mixing precursor; The first mixed precursor comprises a TSPBA solution and a HA-ADH solution, and the second mixed precursor comprises a PVA solution, an OHA solution, and a cobalt metal ion complex solution; The mass-volume concentrations of TSPBA and HA-ADH in the first mixed precursor are both 5% w / v; The mass-volume concentrations of PVA and OHA in the second mixed precursor are both 5% w / v, and the concentration of the cobalt metal ion complex is 2 mg / mL; The volume ratio of the first mixed precursor to the second mixed precursor is 1:1, the volume ratio of the PVA solution to the TSPBA solution is 1:1, and the volume ratio of the OHA solution, HA-ADH solution, and cobalt metal ion complex solution is 1:1:1. Where w / v represents the mass-volume percentage, and mg / mL represents milligrams per milliliter.

[0015] Furthermore, the crosslinking agent TSPBA containing phenylboronic acid groups is a quaternary ammonium salt modified with phenylboronic acid esters generated by the substitution reaction of 4-(bromomethyl)phenylboronic acid and TMPA.

[0016] Compared with the prior art, this application has the following beneficial effects: This invention proposes a sprayable composite hydrogel based on reactive oxygen species response, its preparation method, and its application. By constructing a first dynamic covalent cross-linked network formed by oxidized hyaluronic acid (OHA) and hyaluronic acid-adipic acid dihydrazide (HA-ADH), and a second reversible cross-linked network formed by polyvinyl alcohol (PVA) and a cross-linking agent TSPBA containing phenylboronic acid groups, and loading a specific cobalt metal ion complex into this dual-network composite system, the problems in the aforementioned background technology are effectively solved. In the high-concentration reactive oxygen species environment of the wound, the borate ester bonds in the second cross-linking network undergo responsive breakage, triggering local deconstruction of the composite hydrogel network. This enables the on-demand release of cobalt metal ion complexes, avoiding the passive leakage and systemic toxicity of conventional dressings and significantly improving drug bioavailability. Simultaneously, this dual-network cross-linking structure endows the hydrogel with excellent shear-thinning properties and atomizability, allowing it to be evenly covered on complex and irregular wound surfaces through spraying and rapidly gel in situ to form a physical barrier. This overcomes the shortcomings of traditional hydrogels in effectively adhering to chronic and burn wounds, providing a safe, controllable, and convenient intelligent treatment strategy for wound repair. Attached Figure Description

[0017] Figure 1 This is the 1H NMR spectrum of HA-ADH synthesized in Example 1.

[0018] Figure 2 This is the 1H NMR spectrum of OHA synthesized in Example 2.

[0019] Figure 3 This is the 1H NMR spectrum of TSPBA synthesized in Example 3.

[0020] Figure 4 This is a graph showing the cytotoxicity test results of different metal complexes in Example 4.

[0021] Figure 5 These are the SEM and EDS spectra of the cobalt ion complex in Example 4.

[0022] Figure 6 This is a spraying effect diagram of the PT-OA composite hydrogel in Example 5.

[0023] Figure 7 This is a diagram verifying the POD enzyme activity of the PT-OA composite hydrogel in Example 5.

[0024] Figure 8 This is a graph showing the POD enzyme activity verification of the PT-OA composite hydrogel under different concentrations of H2O2 in Example 5.

[0025] Figure 9 This is a graph showing the CAT enzyme activity verification of the PT-OA composite hydrogel in Example 5.

[0026] Figure 10 This is a diagram showing the antibacterial effect of the PT-OA composite hydrogel in Example 5. Detailed Implementation

[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] Furthermore, in this invention, an element referred to as fixed to or disposed on another element may be directly disposed on the other element, or there may be an intermediate element. When an element is considered to be connected to another element, it may be directly connected to the other element, or there may be an intermediate element present simultaneously. The terms vertical, horizontal, left, right, and similar expressions used herein are for illustrative purposes only and do not represent the only possible implementation.

[0029] The following detailed description, through specific embodiments and in conjunction with the accompanying drawings, further illustrates the ROS-responsive sprayable composite hydrogel and its preparation method provided by the present invention. Those skilled in the art should understand that the specific embodiments described herein are merely for explaining the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. All non-substantial improvements and adjustments made according to the core ideas of the present invention shall still fall within the scope of protection of the present invention.

[0030] Example 1

[0031] This embodiment provides a method for preparing hyaluronic acid-adipic acid dihydrazide (HA-ADH), the specific steps of which are as follows: Accurately weigh 1g of hyaluronic acid and dissolve it in 100ml of LME buffer. Then add 960mg of EDC·HCl and 680mg of HOBt. Activate the solution with magnetic stirring at room temperature for 30 minutes to fully activate the carboxyl groups in the hyaluronic acid molecular chain.

[0032] Then, 4.36 g of adipic acid dihydrazide (ADH) was added to the reaction system, and the reaction was continued to be stirred at room temperature for 24 hours.

[0033] After the reaction was completed, the mixture was placed in a dialysis bag (molecular weight cutoff 8000~14000) and purified by dialysis with deionized water to remove unreacted small molecule impurities and salts. Finally, white spongy HA-ADH solid was obtained by freeze drying.

[0034] The 1H NMR spectrum of the HA-ADH product prepared in this embodiment is shown below. Figure 1 As shown; Figure 1 In comparison with the proton NMR spectrum of hyaluronic acid (HA), the proton NMR spectrum of HA-ADH not only retains the characteristic peak of the methyl group in the original hyaluronic acid structure (chemical shift of approximately 2.0 ppm, labeled as peak a), but also adds the characteristic peak of the methylene group belonging to the adipic acid dihydrazide skeleton (chemical shifts of approximately 1.5 ppm and 2.2 ppm, labeled as peak b and peak c, respectively).

[0035] The presence of the aforementioned characteristic signals fully demonstrates that ADH has been successfully covalently grafted onto the hyaluronic acid molecular chain; and the absence of other obvious impurity peaks in the NMR spectrum indicates that the prepared product has high purity and can be directly used for subsequent hydrogel crosslinking reactions.

[0036] Example 2

[0037] This embodiment provides a method for preparing oxidized hyaluronic acid (OHA), the specific steps of which are as follows: Accurately weigh 1.50 g of hyaluronic acid, add 150 mL of deionized water, and stir until fully dissolved at room temperature to obtain a uniform, transparent, viscous solution. Separately, dissolve 0.5 g of sodium periodate in 10 mL of deionized water, and then slowly add this sodium periodate aqueous solution to the completely dissolved hyaluronic acid solution. Stir continuously for 6 hours under light-protected conditions. During this process, sodium periodate selectively oxidizes the ortho-dihydroxyl groups on the hyaluronic acid molecular chain, cleaving them and introducing aldehyde groups.

[0038] After the reaction was complete, 2 mL of ethylene glycol was added to the system, and the mixture was stirred for another hour to consume the remaining sodium periodate and terminate the oxidation reaction. The reaction product was then transferred to a dialysis bag and purified by dialyzing in deionized water for 3 days, changing the deionized water 6 to 8 times during this period to thoroughly remove reaction byproducts. After dialysis, the solution was freeze-dried to obtain oxidized hyaluronic acid (OHA).

[0039] The 1H NMR spectrum of the product in this embodiment is as follows: Figure 2 As shown, compared with the 1H NMR spectrum of hyaluronic acid raw material, a new signal peak appeared in the 1H NMR spectrum of OHA at a chemical shift of about 5.2 ppm. This signal peak is attributed to the proton in the ortho-hemiacetal structure and is formed by the interaction between the newly generated aldehyde group in the oxidation reaction and the adjacent unoxidized hydroxyl group.

[0040] The clear appearance of this characteristic peak confirms that the ortho-dihydroxyl groups on the hyaluronic acid molecular chain have been successfully partially oxidized to aldehyde groups, thereby obtaining an OHA prepolymer with active aldehyde groups, providing reaction sites for subsequent crosslinking.

[0041] Example 3

[0042] This embodiment provides a method for preparing a crosslinking agent containing phenylboronic acid groups (TSPBA), the specific steps of which are as follows: Accurately weigh 0.5 g of 4-(bromomethyl)phenylboronic acid and dissolve it in a round-bottom flask containing 20 mL of N,N-dimethylformamide (DMF) solution. Then, add 133 μL of TMPA (tris(3-dimethylaminopropyl)amine) to the solution. Place the reaction apparatus in a constant temperature oil bath at 60 °C and stir for 12 hours. In this reaction, 4-(bromomethyl)phenylboronic acid undergoes a substitution reaction with TMPA, introducing phenylboronic acid groups into the TMPA structure through quaternary ammonium salt bonds to form a multi-armed phenylboronic acid crosslinking agent. After the reaction is complete, slowly pour the reaction solution into 40 mL of tetrahydrofuran (THF) solution. Due to the reduced solubility of the product in THF, a large amount of white precipitate precipitates. Then, wash the precipitate 2 to 3 times with 10 mL of THF and filter to remove unreacted small organic molecules. Dissolve the filtered white solid in 5 mL of deionized water and freeze-dry overnight to obtain purified white TSPBA powder.

[0043] The 1H NMR spectrum of the TSPBA prepared in this embodiment is shown below. Figure 3 As shown in the spectrum, spectral analysis revealed aromatic proton signals belonging to the triphenyl skeleton adjacent to the borate ester group within the chemical shift range of 7.50–7.80 ppm; multiple peak signals appearing at chemical shifts of 3.50–4.20 ppm belong to methylene protons directly bonded to oxygen atoms; these two sets of characteristic signal peaks are completely consistent with the target molecular structure of TSPBA, and no obvious residual peaks of 4-(bromomethyl)phenylboronic acid or TMPA were observed in the spectrum, indicating that the synthesized crosslinking agent TSPBA has high purity and meets the requirements for hydrogel preparation.

[0044] Example 4

[0045] This embodiment provides a method for synthesizing cobalt metal ion complexes (KG / Co), the specific steps of which are as follows: Accurately weigh 584.4 mg of α-ketoglutaric acid (α-KG) and dissolve it in 12 mL of methanol; separately, dissolve 421 mg of 4-methylaminothiourea in 16 mL of methanol. After thoroughly mixing the two solutions, the reaction was carried out under constant temperature and magnetic stirring at 50 °C. In this stage, the carbonyl group of α-KG undergoes a nucleophilic addition reaction with the amino group of 4-methylaminothiourea to generate a coordination precursor with a specific coordination configuration. The reaction system was cooled to room temperature, and the purified coordination precursor was mixed with cobalt chloride dihydrate (CoCl2·2H2O) at a 1:1 molar ratio, and the complexation reaction was continued at room temperature. The electron-donating groups such as nitrogen and sulfur in the coordination precursor coordinate with the empty orbitals of cobalt ions to form a stable KG / Co metal complex. After the reaction, the product was purified by recrystallization to remove unreacted raw materials and other impurities, finally obtaining a high-purity cobalt ion complex sample, which can be used for subsequent bioactivity testing.

[0046] The morphology and elemental composition of the prepared cobalt ion complex were analyzed using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) (see [link to SEM]). Figure 5 SEM images showed that the complex exhibited a regular blocky crystal structure with a relatively smooth surface at the microscopic level. EDS spectra showed that elements such as cobalt (Co), carbon (C), and oxygen (O) had a high degree of spatial consistency in the crystal, further verifying the successful preparation of the target complex. Meanwhile, to evaluate the biosafety of the complex, L929 fibroblasts were used, and its cytotoxicity was systematically assessed using the CCK-8 assay. The experiment set up a series of concentration gradients (2, 5, 10, 20 μg / mL) of cobalt ion complex solutions and co-cultured them with L929 cells for 24 hours.

[0047] like Figure 4As shown, even under the test conditions of the highest concentration of 20 μg / mL, the cell survival rate of the cobalt ion complex group remained above 80%, which was significantly better than that of the control group of other metal complexes at the same concentration. This result confirms that the cobalt metal ion complex prepared in this embodiment has excellent cell compatibility and is suitable for in vivo application in wound dressings.

[0048] Example 5

[0049] This embodiment provides a method for preparing PT-OA composite hydrogels and analyzing key technical parameters. The specific steps are as follows: This embodiment elaborates on the preparation process of the composite hydrogel of the present invention and provides an in-depth explanation of the synergistic technical effects brought about by its core formulation parameters.

[0050] Specific preparation steps: The first mixed precursor and the second mixed precursor were prepared at room temperature.

[0051] The first mixed precursor was prepared by mixing 5 wt% TSPBA aqueous solution and 5 wt% HA-ADH aqueous solution in a 1:1 volume ratio. The second mixed precursor was prepared by mixing 5 wt% PVA aqueous solution, 5 wt% OHA aqueous solution and KG / Co complex solution with a concentration of 2 mg / mL in a volume ratio of 1:1:1.

[0052] Subsequently, the first and second mixing precursors were rapidly mixed at a 1:1 volume ratio. After mixing, the mixture was allowed to stand for 15 seconds, after which it quickly completed cross-linking and gelation, ultimately forming a stable PT-OA composite hydrogel. The gel was then sealed and stored at 4°C.

[0053] Technical Principle Analysis and Formulation Effect Explanation: In the above preparation process, the specific concentrations (5wt% and 2mg / mL) and multiple volume ratios (1:1, 1:1:1, 1:1) are one of the core innovative elements of this invention. The key technical effects produced are as follows: To achieve ideal shear-thinning rheological properties: TSPBA (containing phenylboronic acid groups) in the first mixed precursor forms reversible borate ester bonds with the hydroxyl groups of PVA, endowing the system with dynamic crosslinking properties; while OHA and HA-ADH in the second precursor provide a rigid framework by forming dynamic hydrazide bonds; the precise 1:1 volume ratio and 5wt% concentration ensure that the crosslinking density and viscosity of the two precursors are at the optimal balance point. Under external shear (such as spraying), the dynamic crosslinking network quickly dissociates, making the system a flowable fluid, ensuring smooth spraying; after the external force disappears, the crosslinking network quickly recovers, forming a uniform gel barrier in situ, perfectly meeting the clinical needs of sprayable wound dressings.

[0054] Achieving optimal crosslinking site matching: The precise 1:1 volume ratio effectively ensures that the stoichiometric ratio of aldehyde, hydrazide, hydroxyl, and phenylboronic acid groups in the system tends to be reasonable; this ratio ensures that the two networks (hydrazide bond network and borate ester bond network) interweave and overlap in the composite system, forming a stable dual-network crosslinking structure with synergistic enhancement effect, which not only takes into account the sufficient mechanical strength of the hydrogel on the wound surface, but also provides a sufficiently dense responsive crosslinking site to cope with the microenvironmental changes of wound exudate.

[0055] Sprayability and rapid in-situ gelation test: The first and second mixed precursors were respectively loaded into a dual-barrel spray device to simulate clinical wound spraying; Figure 6 As shown, when the two mother liquors are sprayed onto the bottom surface of the glass bottle at a 1:1 volume ratio, the mixture forms a uniform hydrogel barrier with physical isolation on the substrate surface within 15 seconds. This experiment directly demonstrates that the formulation ratio proposed in this application gives the hydrogel precursor excellent fluidity, making it perfectly suitable for atomized spraying equipment, and enabling rapid in-situ gelation. This solves the problem that traditional pre-made hydrogel dressings are difficult to adhere tightly to irregular wounds and large areas are difficult to cover.

[0056] Peroxidase-like (POD) activity and ROS responsiveness assay: Using UV-Vis spectrophotometry with crystal violet (CV) as a chemical indicator, the ability to generate hydroxyl radicals (·OH) in the system was quantitatively detected. Crystal violet is a dye with electron-rich conjugated chromophores and a characteristic absorption peak at 590 nm. During the reaction, ·OH reacts with the chromophores, leading to dye decolorization and a significant decrease in absorbance at 590 nm.

[0057] like Figure 7 As shown, compared with the CV group and the CV+H2O2 group, the most significant decrease in absorbance at 590 nm was observed only in the CV+PT-OA+Co+H2O2 hydrogel experimental group with added cobalt ion complex. This result directly proves that the hydrogel of the present invention can efficiently catalyze the substrate through the loaded cobalt ion complex in the presence of H2O2, exhibiting excellent peroxidase-like activity.

[0058] Furthermore, by changing the concentration of H2O2 in the system, different degrees of oxidative stress in the wound were simulated, such as... Figure 8 As shown, the experimental results indicate that as the H2O2 concentration increases, the absorbance of the system at 590 nm decreases in a concentration-dependent manner. This confirms that the hydrogel of this invention has a strong ROS concentration-responsive catalytic activity, meaning that the catalytic reaction is only initiated in wound areas with severe inflammation and extremely high ROS levels, while remaining relatively inert in normal tissues (low ROS concentration).

[0059] Catalase-like (CAT) activity assay: The ability of the hydrogel to consume H2O2 was detected by the titanium sulfate colorimetric method. The principle is that under acidic conditions, titanium ions will react with the residual H2O2 in the system to form a yellow peroxytitanic acid complex. This complex has a characteristic ultraviolet absorption peak in the 400~450nm wavelength range (especially near 410nm).

[0060] The hydrogel sample of this application was incubated with H2O2 in a 37°C oven for 24 hours, and then the supernatant was added to titanium sulfate solution for a colorimetric reaction; Figure 9 As shown, compared with the PBS+H2O2 control group and the PT-OA+H2O2 blank hydrogel group, the PT-OA+Co complex+H2O2 experimental group had the lightest color, almost transparent, and the UV absorption curve near 410nm decreased significantly. This confirms that the cobalt ion complex hydrogel has excellent CAT-like activity, can consume a large amount of hydrogen peroxide in the wound microenvironment, and effectively alleviate the continuous oxidative stress damage caused by high concentrations of ROS.

[0061] Validation of intelligent synergistic antibacterial performance: Using Staphylococcus aureus as a model strain, the antibacterial performance of the composite hydrogel was comprehensively evaluated by the standard plating method. Five control groups were set up in the experiment, including: control blank group, blank hydrogel group (PT-OA), physically mixed CoCl2 hydrogel group (PT-OA+CoCl2), hydrogel group loaded with the specific cobalt complex of this application (PT-OA+Co), and hydrogel group loaded with cobalt complex and added with H2O2 to simulate the high ROS environment of the wound (PT-OA+Co+H2O2).

[0062] Plate culture results as follows Figure 10 As shown: the control group and the blank hydrogel group plates were covered with dense colonies, indicating that the hydrogel matrix itself does not have antibacterial ability; the number of colonies on the physically mixed CoCl2 group plates was reduced, but a large number of colonies still survived; while the number of colonies in the group loaded with the specific cobalt complex of the present invention was greatly reduced; more importantly, after adding H2O2 to simulate a high ROS microenvironment, almost no colonies were observed in the culture dishes of the PT-OA+Co+H2O2 group.

[0063] This set of comparative experiments intuitively and powerfully demonstrates the core inventive point of the composite hydrogel of this invention: in the high ROS microenvironment of the wound, the borate ester bond in the hydrogel breaks in response, triggering the precise release of the ligand-stable cobalt ion complex; at the same time, the cobalt ion complex, as a catalytic center, utilizes H2O2 in the local exudate of the wound to generate ·OH.

[0064] This synergistic effect of physical release and chemical catalysis achieves a highly efficient and targeted intelligent sterilization effect, fundamentally overcoming the inherent defects of traditional broad-spectrum antibiotic dressings, such as easy bacterial resistance and uncontrollable drug release. The hydrogel dressing provided by this invention has extremely broad application prospects in the precise treatment of chronic wounds and burn wounds.

[0065] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0066] Furthermore, it should be understood that although this specification describes embodiments, each embodiment does not contain only one independent technical solution. This way of describing the specification is only for clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A sprayable composite hydrogel based on reactive oxygen species response, characterized in that, The hydrogel comprises: The first cross-linked network containing dynamic hydrazide bonds is formed by the condensation reaction of oxidized hyaluronic acid (OHA) and hyaluronic acid-adipic acid dihydrazide (HA-ADH); A second crosslinked network containing borate ester bonds is formed by a reversible reaction between polyvinyl alcohol (PVA) and a crosslinking agent TSPBA containing phenylboronic acid groups; And cobalt metal ion complexes loaded in a composite network composed of the first crosslinking network and the second crosslinking network; In an active oxygen environment, the borate ester bonds in the hydrogel break, triggering the responsive release of the cobalt metal ion complex.

2. The hydrogel according to claim 1, characterized in that, The coordination precursor in the cobalt metal ion complex is generated by a nucleophilic addition reaction of 4-methylaminothiourea and α-ketoglutaric acid, and the coordination precursor and divalent cobalt ions are coordinated to form the cobalt metal ion complex.

3. The hydrogel according to claim 1, characterized in that, The first cross-linking network and the second cross-linking network interpenetrate and overlap to form a dual-network cross-linking structure with a synergistic enhancement effect.

4. The hydrogel according to claim 1, characterized in that, The hydrogel exhibits shear-thinning properties, exhibiting a flowable fluid state under shear stress and reverting to a gel state after the shear stress is removed.

5. A method for preparing a sprayable composite hydrogel based on reactive oxygen species as described in any one of claims 1-4, characterized in that, Includes the following steps: (1) Oxidized hyaluronic acid (OHA) and hyaluronic acid-adipic acid dihydrazide (HA-ADH) are mixed and reacted in an aqueous medium to form an initial hydrogel network containing dynamic hydrazide bonds; (2) Add polyvinyl alcohol (PVA) and crosslinking agent TSPBA containing phenylboronic acid groups to the system obtained in step (1), mix and react to form a composite crosslinking network containing reversible borate ester bonds; (3) Introduce the cobalt metal ion complex into the composite system obtained in step (2) and disperse it evenly in the system. Let it stand to form a gel to obtain the composite hydrogel.

6. The preparation method according to claim 5, characterized in that, The reactions in steps (1) and (2) are carried out in an aqueous phase and at a temperature of room temperature to 37°C.

7. The preparation method according to claim 5, characterized in that, The preparation process of the cobalt metal ion complex includes: dissolving 4-methylaminothiourea and α-ketoglutaric acid in organic solvents respectively to carry out substitution reactions to obtain ligand solutions; mixing the ligand solutions with cobalt metal salt solutions, adjusting the pH to alkaline conditions to carry out coordination reactions, and separating and purifying the mixture after the reaction to obtain the cobalt metal ion complex.

8. The use of the hydrogel according to any one of claims 1-4 in the preparation of medical dressings for wound repair.

9. The preparation method according to claim 5, characterized in that, In step (2), the mixing system is formed by mixing a first mixing precursor and a second mixing precursor; The first mixed precursor comprises a TSPBA solution and a HA-ADH solution, and the second mixed precursor comprises a PVA solution, an OHA solution, and a cobalt metal ion complex solution; The mass-volume concentrations of TSPBA and HA-ADH in the first mixed precursor are both 5% w / v; The mass-volume concentrations of PVA and OHA in the second mixed precursor are both 5% w / v, and the concentration of the cobalt metal ion complex is 2 mg / mL; The volume ratio of the first mixed precursor to the second mixed precursor is 1:1, the volume ratio of the PVA solution to the TSPBA solution is 1:1, and the volume ratio of the OHA solution, HA-ADH solution, and cobalt metal ion complex solution is 1:1:

1. Where w / v represents the mass-volume percentage, and mg / mL represents milligrams per milliliter.

10. The hydrogel according to claim 1, characterized in that, The crosslinking agent TSPBA containing phenylboronic acid groups is a quaternary ammonium salt modified with phenylboronic acid esters generated by the substitution reaction of 4-(bromomethyl)phenylboronic acid and TMPA.